representing indonesian diversity in surat dari lembah baliem - tribuana sari (Faculty of Humanities, Universitas Jenderal Soedirman, 2017)
Story books, through the pictures and simple language they use and also the age of their readers, could become a strategic media to promote multiculturalism among children. Multi cultures also mean multi identities of the people living in Indonesia. This article is aimed to dismantle how the identities of children from various cultures in Indonesia in Surat dari Lembah Baliem, a book for children describing Indonesian diversity, are represented. Despite the multicultural values it contains, the stories in this book also show us that Indonesian multicultural diversity implies dynamic communication and tension among the cultural groups it describes. Moreover, the representation still shows stereotypical model that operates against the multicultural idealism it promotes.